2022
DOI: 10.1088/2057-1976/aca543
|View full text |Cite
|
Sign up to set email alerts
|

Organ dose calculator for diagnostic nuclear medicine patients based on the ICRP reference voxel phantoms and biokinetic models

Abstract: The exponential growth in the use of nuclear medicine procedures represents a general radiation safety concern and stresses the need to monitor exposure levels and radiation-related long term health effects in NM patients. In the current study, following our previous work on NCINM version 1 based on the UF/NCI hybrid phantom series, we calculated a comprehensive library of S values using the ICRP reference pediatric and adult voxel phantoms and established a library of biokinetic data from multiple ICRP Public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…We extracted S values for I-123, I-124, I-125, and I-131 from the National Cancer Institute dosimetry system for Nuclear Medicine (NCINM) version 2 [5], where a library of S values calculated using the ICRP reference voxel phantoms is embedded. The S values from NCINM2 were rearranged according to the source regions, r S , defined in the iodine biokinetic models and the target region, r T , defined in ICRP Publication 133 [31].…”
Section: S Valuesmentioning
confidence: 99%
See 3 more Smart Citations
“…We extracted S values for I-123, I-124, I-125, and I-131 from the National Cancer Institute dosimetry system for Nuclear Medicine (NCINM) version 2 [5], where a library of S values calculated using the ICRP reference voxel phantoms is embedded. The S values from NCINM2 were rearranged according to the source regions, r S , defined in the iodine biokinetic models and the target region, r T , defined in ICRP Publication 133 [31].…”
Section: S Valuesmentioning
confidence: 99%
“…Thus, the estimation of normal tissue doses for thyroid cancer patients is essential not only for RAI therapy planning but also for estimation and prediction of radiation-induced adverse effects. Methods and tools to accurately estimate normal tissue doses for thyroid cancer patients using anatomical and radionuclide images have been actively developed [4][5][6][7]. However, as patient-specific dosimetry is not always feasible for epidemiological studies, organ dose estimation often relies on population-based anatomical and biokinetic models which are used to derive absorbed dose coefficients (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have shown variations in effective doses due to photons, electron [20] and 18 F-FDG [21] estimated using a voxel-based model from those estimated using stylized phantoms. The UF/NCI and PRC phantoms have been used to compute SAF values for electrons and photons of various energies [22][23][24], which in turn are used to compute S values and organ doses for medical intake scenarios [24,25]. These studies only focus on dose computation for medical protection pathways such as intravenous and oral administration, while leaving out the inhalation pathway required for radiological protection.…”
Section: Introductionmentioning
confidence: 99%